Single point Linnik white-light spectral microscopic interferometer for surface measurement. (7th June 2018) - Guo, Tong; Yuan, Lin; Chen, Zhuo; Li, Minghui; Fu, Xing; Hu, Xiaotang
Abstract: According to the requirement for high precision surface measurement in complex situations, a single point Linnik type measuring system with long working distance is built based on white-light spectral interferometry. Five-step phase-shifting algorithm is used to extract accurate phase information in the measuring system. Several experiments are conducted to measure the absolute distance and film thickness, verifying the feasibility of the system. It has been achieved that the system can measure the surface form and film thickness with nanoscale accuracy.